2016
DOI: 10.1093/her/cyw046
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of theSmoker’s Health Project: a pragmatic comparative effectiveness trial of tobacco-dependence interventions based on self-determination theory

Abstract: A pragmatic comparative effectiveness trial examined whether extending the duration of a cost-effective, intensive tobacco-dependence intervention designed to support autonomy will facilitate long-term tobacco abstinence. Participants were randomly assigned to one of three tobacco-dependence interventions based on self-determination theory, namely, Intensive Treatment (IT; six contacts over 6 months), Extended Need Support (ENS; eight contacts over 12 months) and Harm Reduction (HR; eight contacts over 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…For example, Williams et al (2006) trained counselors to support smokers in making autonomous decisions to quit, and Cheon et al (2012) trained teachers to display autonomy-supportive behaviors using their autonomy-support training program. Interventions are usually evaluated using relevant outcome measures of the behavior of interest at single or multiple follow-up occasions after the initiation of the intervention (e.g., Williams et al, 2016). Importantly, researchers have also included measures of key theoretical constructs expected to change as a consequence of the intervention.…”
Section: Evidence For Self-determination Theory Interventionsmentioning
confidence: 99%
“…For example, Williams et al (2006) trained counselors to support smokers in making autonomous decisions to quit, and Cheon et al (2012) trained teachers to display autonomy-supportive behaviors using their autonomy-support training program. Interventions are usually evaluated using relevant outcome measures of the behavior of interest at single or multiple follow-up occasions after the initiation of the intervention (e.g., Williams et al, 2016). Importantly, researchers have also included measures of key theoretical constructs expected to change as a consequence of the intervention.…”
Section: Evidence For Self-determination Theory Interventionsmentioning
confidence: 99%
“…In our past work in which we collected messages written mostly by non-Hispanic White smokers (32 out of 39 participants) [ 14 ], mindfulness, religious, and spiritual practices did not emerge from the peer-written messages. Although not exclusive to African American communities, use of spiritual and religious practices, as a coping response to health issues, is often adopted in this group [ 40 ], with positive and promising results in health outcomes [ 43 ]. Other health behavior change studies in African American populations have shown more positive outcomes if participants reported having strong ties within a religious congregation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-determined motivation is consistently associated with improved psychological well-being and with engagement with—and persistence in—a variety of tasks and long-term behaviours ( Ntoumanis et al, 2020 ). Consequently, the concept has been explored in studies in health behaviour change, in areas such as dental hygiene ( Halvari et al, 2019 ), diet, exercise and obesity ( Teixeira et al, 2012a ), diabetes ( Phillips and Guarnaccia, 2020 ) and tobacco cessation ( Williams et al, 2016 ), with generally encouraging results ( Leblanc et al, 2016 ; Sheeran et al, 2020 ; Teixeira et al, 2012b ). We propose that it could present a fruitful psychological framework from which to understand how psychedelics could assist in lifestyle change, especially from a motivational viewpoint.…”
Section: Could Psychedelic Experiences Increase Self-determination?mentioning
confidence: 99%